DIRECTIVE ILLOCUTIONARY AND PERLOCUTIONARY ACTS IN MISSING (2023) MOVIE - Aminnudin, Karina Dwianggita; Kholiq, Muh. (Universitas Gunadarma, 2023)
Communication in speech acts involves not only words but also action. The directive illocutionary is a form of speech act that attempts to persuade the hearer to do something. It refers to a specific statement that contains particular actions. This research aims to examine the occasions of directive illocutionary by Searl and perlocutionary acts by Austin in the Missing (2023) movie describing how the speaker carries their intention and how the interlocutor responds to the utterances as the action. The researcher used descriptive qualitative method. The data for analysis was obtained from the script dialogue of the Missing (2023) movie. The results of this research showed there are 83 data contained the 6 types of directive illocutionary acts, those are: Asking (41), Commanding (17), Requesting (7), Forbidding (5), Begging (6), and Suggesting (7). There are 40 successful perlocutionary acts and 37 unsuccessful perlocutionary acts that occurred in the movie.